Problem Solving for Women Victims of Domestic Violence: Descriptive Analysis with JASP Based on Demographics - N Cici Mahruliana; Hariyani Hariyani; Yuda Syahputra (Psychocentrum Review, 2020)
Problem solving must be owned by everyone, because in life everyone must have a problem, for that the importance of improving problem solving skills. This study focuses on women who are victims of domestic violence. The effects of domestic violence are a matter of concern, because some victims prefer to be quiet rather than sharing family problems with others or counselors. This research uses a quantitative approach with descriptive methods. Sampling uses a purposive sampling technique that is using certain criteria. The number of samples was 64 people (ages ranging from 25-56 years). The instrument used was a problem harassment instrument for victims of domestic violence who had 34 items. The results showed a solution to the problem of victims of domestic violence from counseling, ethnicity, and education services, M = 106.45, Md = 106.00, Mode = 85.00. Women victims of domestic violence who have done counseling and counseling services are better able to solve family problems than those who have never had counseling, and education influences the problem solving of women victims of domestic violence.